Report of the procedure of voluntary interruption of pregnancy at a university hospital in Uruguay - Ana Bentancor; Ana Laura Hernández; Yamile Godoy; Juan J Dapueto (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the constitution and operation of a voluntary interruption of pregnancy team of a university hospital, from the outlook of the mental health team. METHODS In this case study, the following aspects were analyzed: 1) historical background; 2) implementation of Law 18,897 of October 22, 2012; and 3) functioning of the program at the Hospital de Clínicas of the Facultad de Medicina (Universidad de la República, Uruguay), taking into account three dimensions: structure, process, and results. RESULTS Between December 2012 and November 2013, a total of 6,676 voluntary interruptions of pregnancy were reported in Uruguay; out of these, 80 were conducted at the Hospital de Clínicas. The patients' demographic data agreed with those reported at the national level: Of the total patients, 81.0% were aged over 19 years; 6.2% decided to continue with the pregnancy; and only 70.0% attended the subsequent control and received advice on contraception. CONCLUSIONS In its implementation year in Uruguay, we can assess the experience as positive from the point of view of women's health. Our experience as a mental health team at the Hospital de Clínicas, inserted into the multidisciplinary voluntary interruption of pregnancy team, is in the process of assessment and reformulation of practices.